Insights into the Modulation of Dopamine Transporter Function by Amphetamine, Orphenadrine, and Cocaine Binding - Cheng, Mary Hongying; Block, Ethan; Hu, Feizhuo; Cobanoglu, Murat Can; Sorkin, Alexander; Bahar, Ivet (Frontiers in Neurology, 2015)
Human dopamine transporter (hDAT) regulates dopaminergic signaling in the central nervous system by maintaining the synaptic concentration of dopamine (DA) at physiological levels, upon reuptake of DA into presynaptic terminals. DA translocation involves the co-transport of two sodium ions and the channeling of a chloride ion, and it is achieved via alternating access between outward-facing and inward-facing states of DAT. hDAT is a target for addictive drugs such as cocaine, amphetamine (AMPH) and therapeutic antidepressants. Our recent quantitative systems pharmacology study suggested that orphenadrine (ORPH), an anticholinergic agent and anti-PD drug, might be repurposable as a DAT drug. Previous studies have shown that DAT-substrates like AMPH or -blockers like cocaine modulate the function of DAT in different ways. However, the molecular mechanisms of modulation remained elusive due to the lack of structural data on DAT. The newly resolved DAT structure from Drosophila melanogaster opens the way to a deeper understanding of the mechanism and time evolution of DAT-drug/ligand interactions. Using a combination of homology modeling, docking analysis, molecular dynamics simulations and molecular biology experiments, we performed a comparative study of the binding properties of DA, AMPH, ORPH and cocaine, and their modulation of hDAT function. Simulations demonstrate that binding DA or AMPH drives a structural transition towards a functional form predisposed to translocate the ligand. In contrast, ORPH appears to inhibit DAT function by arresting it in the outward-facing open conformation. The analysis shows that cocaine and ORPH competitively bind DAT, with the binding pose and affinity dependent on the conformational state of DAT. Further assays show that the effect of ORPH on DAT uptake and endocytosis is comparable to that of cocaine.